2023
DOI: 10.48550/arxiv.2301.05843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leveraging Large Language Models to Power Chatbots for Collecting User Self-Reported Data

Abstract: Large Language Model How's your day so far? Prefix 📄 Information format 🤖 Persona modifier A Ongoing Dialogue History Insert as prompt Generate chatbot response B Work & Productivity ✅ Work done ✅ Rate productivity ✅ Other concerns at work ✅ What went well a C Going splendid so far. How is yours? I'm doing well, thanks for asking. Let's talk about your work and productivity yesterday. What work did you get done?Figure 1: An overview of our chatbot running on a large language model through zero-shot response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Several previous applications demonstrated that this model can be meaningfully used for grammar correction, summarizing, answering questions, parsing unstructured data, classification, and translation (Radford et al, 2019;Brown et al, 2020), among other tasks. LLMs have also been used to build chatbots to capture self-reported user data chatting (Wei et al, 2023). However, since the model cannot reason, solve mathematical and ethical questions, or pass the Turing test (Floridi and Chiriatti, 2020), it is regarded as a human-like text generator rather than a general AI in the strict sense.…”
Section: Chatbots and The Automation Of Conversationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous applications demonstrated that this model can be meaningfully used for grammar correction, summarizing, answering questions, parsing unstructured data, classification, and translation (Radford et al, 2019;Brown et al, 2020), among other tasks. LLMs have also been used to build chatbots to capture self-reported user data chatting (Wei et al, 2023). However, since the model cannot reason, solve mathematical and ethical questions, or pass the Turing test (Floridi and Chiriatti, 2020), it is regarded as a human-like text generator rather than a general AI in the strict sense.…”
Section: Chatbots and The Automation Of Conversationmentioning
confidence: 99%
“…A reason that could underlie this finding is that there is evidence suggesting that people are more willing to share information through chatbots (Lee et al, 2020), which are generally believed to be useful for collaboration (Kim et al, 2021). Together with LLMs such as GPT-3, recent research has explored the usability of these models in operating chatbots (Wei et al, 2023). In line with this novel technology, in the present study, we empirically test a chatbot framework that may be more effective than survey methods for eliciting meaningful responses from participants in the context of urban design.…”
Section: Comparisons Of Chatbots and Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advancements in LLMs [25] offer great possibilities for social robotics [20,26,27]. These models excel in conducting natural, human-like dialog, as evident in applications like chatbots and virtual agents [24]. However, unlike virtual agents, social robots possess physical embodiment and distinct personalities.…”
Section: Llm-driven Conversationsmentioning
confidence: 99%
“…In fact, with closed-ended questions (which PROMs essentially are), the chatbots collect the same quality, if not higher, compared with digital surveys [ 33 , 82 ]. The solutions conducting interviews with open-ended questions generate more noise (less precise data); however, compared with the closed-ended solutions, their participants showed higher engagement and provided higher-quality responses when engaged with the chatbot [ 83 , 84 , 85 ]. With the recent breakthrough in large language models (LLMs), e.g., OpenAI’s GPT3, Google’s PALM, Gopher, Bing Chat, and Azure Health Bot, etc.…”
Section: Related Workmentioning
confidence: 99%